Dampak Kompensasi finansial langsung (TPP) Terhadap Kinerja Pergawai : Kepuasan Kerja Sebagai Mediasi di Sekretariat Daerah Kota Jambi - Putra, Rizky Eka; Adriani, Zulfina; Octavia, Ade (Sekretariat Pusat Lembaga Komunitas Informasi Teknologi Aceh, 2025)
The purpose of this study was to determine and describe the description of direct financial compensation (TPP), job satisfaction and employee performance at the Jambi City Regional Secretariat, the analytical tool used was PLS analysis. The results showed an overview of direct financial compensation (TPP) at the Jambi City Regional Secretariat as a whole, it can be concluded that the majority of employees said they agreed that the TPP provided in accordance with the physical ability to work, the volume of work, security, safety, and innovation owned by employees and performance according to the target. Overall job satisfaction can be concluded that the majority of employees say they agree that employees are satisfied working because of the amount of allowances received, the speed of payment of allowances, the suitability of allowances with employees' abilities, and the support of superiors and getting fair treatment from superiors. Meanwhile, overall employee performance can be concluded that the majority of employees said they agreed that there is a good ability to do work, a good level of work, work results in accordance with orders, can do a large amount of work, consistently, on time and manage time effectively and efficiently and and optimize work results. Direct financial compensation (TPP) has a positive and significant effect on employee performance. Direct financial compensation (TPP) has a positive and significant effect on job satisfaction. Job satisfaction has a positive and significant effect on employee performance. Direct financial compensation (TPP) has a positive and significant effect on employee performance through employee job satisfaction at the Jambi City Regional Secretariat.